T4 A cross-sectional analysis of the effect of COPD on work capability using the birmingham COPD cohort. (14th November 2013) - Kalirai, K; Adab, P; Jordan, R; Fitzmaurice, D; Ayres, J
Abstract : Introduction: The effect of COPD on work is poorly understood. Approximately 40% are of working age, however, employment rates are lower compared to others. Little is known about characteristics of COPD patients who remain in employment compared to those who do not. Aim: To assess which factors are associated with employment status among working age COPD patients. Methods: 2000 patients with COPD from primary care are being recruited into a three-year cohort study. In addition to clinical data, occupational history and work performance are assessed. Interim baseline data was used to assess associations between employment status, co-morbidities, COPD assessment test (CAT) scores (impact of COPD on HRQL), lung health, BMI and exercise capacity among COPD patients of working age. Results: Of the 1094 patients recruited 31.8% (n = 348) were of working age (mean age 54.9), of whom 31.6% (n = 110) were in work. Compared to those not in work, working patients were more likely to be male (72.7% vs 52.5%) but were similar in terms of smoking history (ever smokers: 94.4% vs 91.3%). Overall, working patients had fewer co-morbidities. Adjusted for age, sex and smoking status, they were less likely to have cardiovascular disease (OR = 0.58; 95% CI 0.38 0.87), gastro-intestinal disease (OR = 0.37; 0.20 0.69), cancer (OR = 0.09; 0.01 0.72)) and osteoarthritis (OR = 0.4; 0.19 0.84). Being in work was associated with less dyspnoea (OR = 0.12; 0.05 0.25 for MRC grade 1 vs. grade 5), higher quality of life (OR = 0.34; 0.14 0.85 for low vs. very high CAT score) and a greater exercise capacity (OR = 1.14; 1.08 1.19), but BMI was not associated with employment status (OR = 1.0; 0.97 1.06). There was no difference in disease severity (assessed by GOLD stage) between the two groups (p for trend = 0.16). Conclusions: This is the first primary care study in the UK to consider the impact of COPD on work capability. COPD patients who are in work tend to be healthier, are less breathless and have a better quality of life than those not in work, even though disease severity in the two groups was similar. The findings from this analysis suggest that being in work is good for health but longitudinal studies are needed to confirm this.